Risk Factors for Cognitive Impairment after Ischemic Stroke - Saphira Nurani, Rr R; Martini, S (KnE Life Sciences, 2018)
Stroke can cause cognitive impairment. Cognitive impairment is brain function disorder that includes impaired orientation, attention, concentration, memory, language and intellectual functions. The aim of this research was to analyze the risk factors for cognitive impairment after ischemic stroke based on risk factors such as age, gender, educational level, record of hypertension, exposure to cigarette smoke, medication adherence, and sleep pattern in ischemic stroke patients in Hajj General Hospital Surabaya. This study is an observational analytic study with case control design. Respondents consisted of 38 cases and 38 control selected through accidental sampling. Data were obtained from questionnaires named Mini Mental State Examination (MMSE) questionnaire and the Pittsburg Sleep Quality Index (PSQI) questionnaire. The independent variables in this study are age, gender, educational level, record of hypertension, exposure to cigarette smoke, medication adherence, and sleep pattern. The analysis in this study used OR calculation on Epi Info with significance level 95% CI. The results showed that cognitive impairments in poststroke ischemic’s risk are age (OR = 3,43; 95% CI = 1,08 < OR < 10,89), sex (OR = 2,67; 95% CI = 1.05 < OR < 6,83), educational level (OR = 4,17; 95% CI = 1,60 < OR < 10,86), record of hypertension (OR = 1,60; 95% CI = 0,62 < OR < 4,17), exposure to cigarette smoke (OR = 1,24; 95% CI = 0,50 < OR < 3,04), medication adherence (OR = 6,59; 95% CI = 2,23 < OR < 19,43), and sleep pattern (OR = 8,125; 95% CI = 2,88 < OR < 22,93). The research results showed that age, gender, level of education, medication adherence, and sleep pattern have a significant OR values and record of hypertension as well as exposure to cigarette smoke have insignificant OR values. Ischemic stroke patient is suggested to maintain medication compliance and sleep pattern. Keywords: ischemic stroke, cognitive impairment, risk factors, demographic factors, vascular factors